Thermodynamic study of improved cooling in solar photovoltaic cells using nanofluids with graphite-doped titanium dioxide and aluminum oxide - N. Sathiesh Kumar; Debabrata Barik; Kapura Tudu; Seepana Praveenkumar; Milon Selvam Dennison; Talib K. Ibrahim (Case Studies in Thermal Engineering)
Maximizing energy collection and optimizing the performance of solar photovoltaic cells (SPVCs) is essential for the day. In this context, using nanofluids of graphite-dopped titanium dioxide (G-TiO2) and aluminum oxide (G-Al2O3) in SPVC systems plays a crucial role in preventing PV panel overheating, thereby enhancing electrical efficiency and the panel's life span. For this purpose, the ultrasonication technique was used to dope graphite with TiO2 and Al2O3 and mixed with deionized water (DI-H2O) at concentrations of 0.5, 0.6, 0.7, and 0.8 % by vol. The results indicated that G-Al2O3 seems to give optimum results compared to G-TiO2. With G-Al2O3 the electrical and thermal efficiencies were increased to 16.2 % and 27.2 %, this is about 5.1 % and 6.3 % higher than the DI-H2O. With nanoparticle volume concentration of 0.7 %, G-Al2O3 causes a 3 % higher pressure drop, 3.6 % higher in friction factor, 8.6 % higher in Nu, and 9.5 % higher in temperature gradient (ΔT/Δx) in comparison to G-TiO2 at 14 h respectively. Hence it can be recommended that, with an increase in pump efficiency or by the use of a variable-speed pump, the extra resistance can be compensated for without excessive energy consumption.